Vertical and time distribution of Pseudoscorpiones (Arthropoda: Arachnida) in a floodplain forest in the Brazilian Pantanal - Battirola, Leandro Dênis (2017)
Pseudoscorpions embrace a diverse group of arachnids with approximately 3 500 species that occur in various habitats, such as soil, leaf litter, caves and canopies. This study aimed at evaluating the relationship between the pseudoscorpion assemblages in soil, termite nests, tree trunks and canopies, as well as the temporal distribution as to the abundance and richness of species in these habitats. For this purpose different sampling techniques were applied in an integrated manner in distinct habitats of a seasonally flooded monodominant forest in the Northern Pantanal of Mato Grosso, Brazil. Data regarding the abundance and richness of assemblage species were organized by means of the Non-Metric Multidimensional Scaling (NMDS). A total of 2 068 Pseudoscorpiones distributed in seven families and 18 species were captured. Chernetidae (8 spp.) and Withiidae (5 spp.) predominated, while Atemnidae, Cheiridiidae, Geogarypidae, Lechytiidae and Olpiidae were present with only one species each. Terrestrial fauna was more abundant (1 035 ind.; 50.0 % of the total catch) with three families and 10 species. In the arboreal fauna (712 ind.; 34.4 %), four families and 13 species were found. Termite mounds (321 ind.; 15.6 %) corresponded to the habitat with the least number of individuals, however, five families and nine species were identified, including Parachernes sp. 2, Geogarypus sp. and Olpiolum sp., not found in other analyzed habitats in this forest. The analyses did not show any temporal variation as to abundance or richness of Pseudoscorpiones in each evaluated habitat; however, the analysis showed that the edaphic environment (soil + termite nests), tree trunks and tree canopies are distinct habitats in relation to the composition of the assemblage. The occurrence of typical terricolous (e.g. Parawithius sp., Withiidae gen. sp. and Parachernes sp.) and other arboricolous (e.g. Cheiridium sp., Americhernes sp. and Lustrochernes sp.) species highlights the vertical stratification of the assemblage present in this floodplain forest in the Pantanal of Mato Grosso.